Pidana Penjara Untuk Anak Pelaku Tindak Pidana Terorisme dalam Perspektif Perlindungan Anak - Purnomo, Didik; Djatmika, Prija; Aprilianda, Nurini (Universitas Negeri Malang, 2022)
This study aimed to analyze imprisonment for children who were perpetrators of terrorism crimes and legal protection for children who were perpetrators of terrorism crimes based on statutory regulations. The study was analyzed qualitatively using a statutory approach and a case approach with a normative juridical type of research. The study results showed that imprisonment for children who were perpetrators of terrorism criminal in the Juvenile Criminal Justice System Act was not prohibited but must be used as a last resort and in the shortest time. Legal protection for children involved in criminal acts of terrorism in the Child Criminal Justice System Act was in line with the Child Protection Act, which considered special protection for children who were perpetrators of terrorism crimes by emphasizing rehabilitation through deradicalization guided by religious education, Pancasila education, values of nationalism and guidance on the dangers of terrorism.